Latitudinal gradients in intraspecific ecological diversity - Araujo, Marcio S. [UNESP]; Costa-Pereira, Raul (Royal Soc, 2013)
The increase in the number of species with decreasing latitude is a striking pattern of global biodiversity. An important feature of studies of this pattern up to now has been the focus on species as the fundamental unit of interest, neglecting potential within-species ecological diversity. Here, we took a new perspective on this topic by measuring the degree to which individuals within populations differ in niche attributes across a latitudinal gradient (range: 54.01 degrees S to 69.12 degrees N). We show that 156 populations of 76 species across a wide range of vertebrate and invertebrate animal taxa contain more ecologically diverse assemblages of individuals towards lower latitudes. Our results add a new level of complexity to our understanding of global patterns of biodiversity and suggest the possibility that niche variation is partly responsible for the latitudinal gradients of species diversity.
Keywords: biodiversity; individual specialization; niche packing; niche variation